Characterization of gross composition, energy value, and fatty acid profile of milk from lowland tapir (Tapirus terrestris) during different lactation periods - Van Nieuwenhove, Carina Paola (2014)
We evaluated gross composition, energy value, and fatty acid profile of colostrum, transitional, and mature milk of lowland tapir (Tapirus terrestris (L., 1758)) from Argentina. Samples were obtained from six healthy animals kept in captive or semicaptive conditions. Protein content varied over time from 6 to 19 g/100 g of milk; carbohydrates varied from 2.4 to 5.4 g/100 g of milk; fat varied from 2.4 to 17.3 g/100 g of milk. Energy value also varied over time, with colostrum having the highest value.Fatty acid profile revealed a unique pattern in tapir milk, characterized by the presence of higher amounts of lauric, myristic, and pentadecanoic acids than in milk from other equids. Traces of conjugated linoleic acid (CLA) were measured, being the only trans fatty acid detected in tapir milk. Neither butyric acid (C4:0) nor fatty acids longer than C18 were found in tapir milk. The characteristics of tapir milk include high concentration of fat, caseins, and whey proteins. Gross composition and saturated fatty acid to unsaturated fatty acid (SFA/UFA) ratio of tapir milk were more similar to that of horse milk than rhinoceros milk. The present study sheds light on tapir fatty acid metabolism and on nutritional requirements of their newborns, which can be used to improve conservation and management strategies. Furthermore, different periods of lactation were evaluated in this species for the first time, thus contributing to the general knowledge of milk from other members of the order Perissodactyla